A phenomenon of environmental security: categorical and conceptual approaches in the context of public governance - Radchenko, Oksana (Pressing Problems of Public Administration, 2023)
The article analyzes the phenomenon of environmental safety as one of the most important issues of today’s reality, which reflects the impact of human activity in various fields on the surrounding natural environment, which is an acute and urgent problem of our time, which actualizes the need for scientific understanding of the phenomena and processes of both global environmental changes and direct human influence on the state of the environment in the context of public management and regulation of the processes of ensuring the environmental security of national states and the entire world community. The purpose of the research is to elaborate and systematize scientific categories, concepts and definitions of the sphere of public management and administration, related to the issues of ensuring environmental safety. Due to the wide scientific attention and the intensity of the disclosure of the problems of the phenomenon of ecological safety in the scientific discourse, there is an inevitable conflict in the interpretation and understanding of certain scientific categories and definitions of a logical chain of concepts related to the root concept, which in this case is ecological safety. A certain solution to this scientific contradiction is the disclosure of the interrelationship of the main definitions of the categorical-conceptual apparatus of public administration in the context of scientific attention to two interdependent and at the same time relatively independent branches of the root concept of “environmental safety”, where the first considers the safety of a person and his life activities, proposed in this article. and the second is security in the state dimension. Some academic discourse on environmental security issues demonstrates different approaches and visions of related categories and concepts, but is unified in the understanding that in the modern philosophy of public management, the cornerstone of effective management should be sustainable development based on caring for nature, reducing the anthropological burden on the noosphere, rational use of natural resources with a gradual transition from hydrocarbon energy to renewable, balanced human interaction with the living environment for future generations.